The Potential of Trichosanthes tricuspidata Lour. from Bangli, Baturiti, Bali for Free Radicals Scavenging - Arrohmatus Syafaqoh Li'aini; Farid Kuswantoro; Aninda Retno Utami Wibowo; Cokorda Istri Meyga Semarayani; Putri Kesuma Wardhani (Journal of Tropical Biodiversity and Biotechnology, 2022)
In addition to the studies on potential medicinal uses of Trichosanthes, a screening on phytochemical compounds and antioxidants activity of Trichosanthes tricuspidata from Bangli, Baturiti, Bali, Indonesia, was conducted on its leaves, fruits, peels, and seeds. Qualitative phytochemical tests were conducted to find out the chemical constituents of T. tricuspidata, while its antioxidant activity was tested by applying DPPH (1,1-diphenyl-2-picrylhydrazyl radical) method. As a result, flavonoid, alkaloid, terpenoid, tannin, and saponin were present in all methanolic extracts of T. tricuspidata. Furthermore, the best antioxidant activity was exhibited by peel extract. After all, T. tricuspidata contains a prospective compound agent for medicinal use.